Diasporas and conflict: distance, contiguity and spheres of engagement. (3rd April 2017) - Van Hear, Nicholas; Cohen, Robin
Abstract: Diasporas are now well-established players in the global political economy, yet their role in conflict and post-conflict settings remains controversial. Diasporas have variously been described as war-mongers, peace-builders, or ambivalent in their influence on conflict. We suggest that this variety of characterizations might be explained by disaggregating forms of diaspora engagement and the public and private spaces in which they occur into three 'spheres of engagement'. We then go on to consider two variants of conflict-related diasporas: 'distant diasporas', alluding particularly to Sri Lanka, Afghanistan and Somalia, and 'contiguous diasporas', referring mainly to the Russian-speaking peoples in the former Soviet Union but also to groups like the Kurds spread across several nation-states. We show that different forms and levels of engagement generate varying levels of demand on diasporan households. Differences of wealth, resources, social capital and class also influence the capacity of diasporas to engage in conflict and post-conflict roles.